Periprosthetic Joint Infection of Hip and Knee: A Review of Current Concepts - Rattanaprichavej, Piti (Naresuan University Journal: Science and Technology (NUJST); Vol 23 No 1 (2015): January-April 2015, 2015)
Total joint arthroplasty is a successful and recently developed procedure performed on an increasing number of patients. However, periprosthetic joint infection (PJI) is a calamitous complication of this operation, the incidence of which is 1-2%. Different investigators have defined numerous definitions for this complication, but the Musculoskeletal Infection Society (MSIS) definition of PJI has been most widely used. Management of PJI ranges from antibiotic suppression alone to two-stage revision surgery depending on the onset and duration of infection. Currently, investigation focuses on early diagnosis of PJI by multiple indicators in order to diminish the severity of this complication. Fungal PJI and culture-negative PJI are even more rare but much difficult to treat than typical PJI. Knowledge of the association between PJI and bacterial biofilm appears to be an emerging concept for the diagnosis and management of PJI. Keywords : Periprosthetic joint infection, PJI, infected TKA, infected THA, revision TJA
Keywords: Periprosthetic joint infection, PJI, infected TKA, infected THA, revision TJA